(untitled) (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of factors related to the audit firms’ environment on external auditor change in Libyan joint-stock companies from the perspective of external auditors. These factors include competition among audit firms, audit fees, auditor independence, and the regulatory and supervisory framework. The study adopts a descriptive-analytical approach and uses a questionnaire as the primary tool for data collection from a sample of external auditors. A set of statistical techniques is employed, including descriptive statistics, Pearson correlation, one-way (ANOVA) and multiple linear regression analysis. The findings reveal significant positive relationships between all dimensions of the audit firms’ environment and external auditor change. The regression results indicate that these factors have a statistically significant impact, with auditor independence being the most influential factor, followed by competition among audit firms, audit fees, and the regulatory framework. The results also show significant differences attributed to educational qualification, while no significant differences are found with respect to years of experience. Based on these findings, the study recommends enhancing auditor independence, regulating competition among audit firms, and strengthening the regulatory framework to improve audit quality and ensure stability in auditor-client relationships.